GAMBARAN SIKAP IBU DALAM MENCEGAH COVID-19 PADA ANAK BALITA - Rezky Rizalti; Arneliwati Arneliwati; Ganis Indriati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2022)
Coronavirus Disease-2019 (COVID-19) is an infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV 2). The spread of COVID-19 is so fast that it is easy to infect toddlers. Mothers have a vital role in protecting their children from COVID-19. This study aims to determine the description of mothers' attitudes in preventing COVID-19 in toddlers. The research design is descriptive quantitative research with a cross-sectional approach. Data was collected using a questionnaire consisting of 17 statements about mothers' attitudes in preventing COVID-19 in toddlers and given to 173 respondents with toddlers aged 12 - 59 months in North Tangkerang, Pekanbaru. The data analysis using a simple descriptive presented in the frequency distribution table. The results showed that the mother's attitude was in the positive category with a total of 89 respondents (51,4%). It can be concluded that mothers with toddlers aged 12 - 59 months in North Tangkerang, Pekanbaru have positive attitudes in preventing COVID-19. This research is expected to contribute to nursing science regarding mothers' attitudes in preventing COVID-19 in toddlers.Keywords : Attitudes, COVID-19, Mothers, Toddlers